Hyperoxia Provokes Time- and Dose-Dependent Gut Injury and Endotoxemia and Alters Gut Microbiome and Transcriptome in Mice - Li, Yunhang; Tao, Yuanfa; Xu, Jingyu; He, Yihuai; Zhang, Wen; Jiang, Zhigang; He, Ying; Liu, Houmei; Chen, Miao; Zhang, Wei; Xing, Zhouxiong (Frontiers in Medicine, 2021)
Background: Oxygen therapy usually exposes patients to hyperoxia, which induces injuries in the lung, heart and brain. Gut and gut microbiome play key roles in critical illnesses, but the impact of hyperoxia on gut and gut microbiome remains not very clear. We clarified the time- and dose-dependent effects of hyperoxia on the gut and investigated oxygen-induced gut dysbiosis and explored the underlying mechanism of gut injury by transcriptome analysis. Methods: C57BL/6 mice were randomly divided into the control group and nine different oxygen groups exposed to hyperoxia with an inspired O2 fraction (FiO2) of 40%, 60% and 80% for 24 h, 72 h and 168 h (7 d), respectively. Intestinal histopathological and biochemical analysis were performed to explore the oxygen-induced gut injury and inflammatory response. Another experiment was performed to explore the impact of hyperoxia on gut microbiome by exposing the mice to hyperoxia (FiO2 80%) for 7 d, with 16S rRNA sequencing method. We prolonged the exposure (up to 14 d) of the mice to hyperoxia (FiO2 80%), and gut transcriptome analysis and western blotting were carried out to obtain differentially expressed genes (DEGs) and signaling pathways related to innate immunity and cell death. Results: Inhaled oxygen induced time- and dose-dependent gut histopathological impairment characterized by mucosal atrophy (e.g., villus shortening: FiO2 80% for 24 h: P = 0.008) and enterocyte death (e.g., apoptosis: FiO2 40% for 7 d: P = 0.01). Administered oxygen time- and dose-dependently led to intestinal barrier dysfunction (e.g., endotoxemia: FiO2 80% for 72 h: P = 0.002) and potentiated gut inflammation by increasing proinflammatory cytokines (e.g., TNF-α: FiO2 40% for 24 h: P = 0.003) and reducing anti-inflammatory cytokines (IL-10: FiO2 80% for 72 h: P < 0.0001). Hyperoxia induced gut dysbiosis with an expansion of oxygen-tolerant bacteria (e.g., Enterobacteriaceae). Gut transcriptome analysis identified 1747 DEGs and 171 signaling pathways and immunoblotting verified TLR-4, NOD-like receptor and apoptosis signaling pathways were activated in oxygen-induced gut injury. Conclusions: Acute hyperoxia rapidly provokes gut injury in a time- and dose-dependent manner and induces gut dysbiosis, and innate immune response is involved in oxygen-induced gut injury.